The Ability of Shiga Toxin-Producing Escherichia coli to Grow in Raw Cow’s Milk Stored at Low Temperatures - Lene Idland; Erik G. Bø-Granquist; Marina Aspholm; Toril Lindbäck (Foods, 2022)
Despite the lack of scientific evidence, some consumers assert that raw milk is a natural food with nutritional and immunological properties superior to pasteurized milk. This has led to the increased popularity of unpasteurized cow milk (UPM) and disregard for the risks of being exposed to zoonotic infections. Dairy cattle are healthy carriers of Shiga toxin (Stx)-producing E. coli (STEC), and contaminated UPM has caused STEC outbreaks worldwide. The association between STEC, carrying the eae (E. coli attachment effacement) gene, and severe diseases is well-established. We have previously isolated four eae positive STEC isolates from two neighboring dairy farms in the Southeast of Norway. A whole genome analysis revealed that isolates from different farms exhibited nearly identical genetic profiles. To explore the risks associated with drinking UPM, we examined the ability of the isolates to produce Stx and their growth in UPM at different temperatures. All the isolates produced Stx and one of the isolates was able to propagate in UPM at 8 °C (p < 0.02). Altogether, these results highlight the risk for STEC infections associated with the consumption of UPM.